Hubungan Dukungan Suami Dan Peran Tenaga Kesehatan Dengan Penggunaan Alat Kontrasepsi Dalam Rahim (AKDR) Di Klinik Pratama Hanna Kasih Kecamatan Medan Timur - Yasrida Nadeak (Pusat Riset dan Inovasi Nasional, 2023)
The high number of births in Indonesia is worrying many parties. Since 2004 the Family Planning (KB) program is considered to be slow, until the birth rate reaches 4.5 million per year. The family planning program is one of the government's policies in the field of population. This study aims to determine the relationship of role’s husband and role’s health workers in utilizing contraception (IUD). This research was a descriptive analytic study with a cross-sectional approach. The sample in this study is all birth control acceptors in July 2018 amounted 42 respondents. Data Analysis using chi square test. The results showed that respondents who used IUD were 12 respondents, and those who did not use IUD were 30 respondents. There is a relationship between the p value of the role of husband is .031 and the the role of health workers is .020. The conclusion of this study is that there is a significant relationship between the role of husband, and the role of health workers in utilizing contraception (IUD). it is recommended to husbands are more be motivated and support mothers to utilizing the IUD, and the health workers hold counseling to increase public knowledge about contraception.